2009
DOI: 10.1016/j.crci.2008.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the occurrence and reactivity of the carbonate radical in surface freshwater

Abstract: A model was developed to foresee the degradation kinetics of dissolved compounds for reaction with the carbonate radical in surface waters. It would contribute to the assessment of the environmental persistence of pollutants, therefore allowing a better definition of the exposure of natural ecosystems and human communities to hazardous substances. The model is a function of the water chemical composition, the water column depth, and the second-order rate constant of the reaction between the relevant compound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…The same compounds could also undergo significant transformation by CO 3 −• in the environment (Vione et al, 2009b …”
Section: Reaction With Comentioning
confidence: 99%
“…The same compounds could also undergo significant transformation by CO 3 −• in the environment (Vione et al, 2009b …”
Section: Reaction With Comentioning
confidence: 99%
“…The formation rate of CO 3 −• in reaction (13) is given by (Canonica et al, 2005;Vione et al, 2009a):…”
Section: Hydroxyl Radicals • Ohmentioning
confidence: 99%
“…As far as indirect photochemical processes are concerned, they depend as molecular features, on the reactivity between the target molecule and the various photogenerated transients, and on water chemical composition and light penetration as environmental features (Hoigné, 1990). In the case of the sensitised reactions involving • OH and CO 3 −• , the role of the environmental features can be as important as, or even more important than that of molecular reactivity (Vione et al, 2009a and2010a). Therefore, it is suggested that environment-dependent parameters such as water chemical composition and column depth can play a major role in indirect photochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it can be hypothesized that either PAH oxidation is carried out at the soil surface (no homogeneous scavenging of HO ) or/and radical carbonates formed in Equations (2) and (3) are capable of oxidizing the extracted PAHs in solution. Reactivity of carbonate radicals with organic molecules has been previously reported in the literature (Vione et al, 2009;Merouani et al, 2010). Alternatively, carbonate radicals can generate hydroperoxyl radicals according to:…”
Section: Spc Treatment Of Contaminated Soilmentioning
confidence: 97%